Handbook of research on digital marketing innovations in social entrepreneurship and solidarity economics - Sáiz Álvarez, José Manuel (Business Science Reference, 2019)
"This book explores the relationship between digital marketing, social entrepreneurship, and solidarity economics to create crowding-in effects and socioeconomic wealth directed towards the improvement of the standard of living of the society. It also examine examines the impact and application of digital marketing on small and medium enterprises"--